SISTEM PENDUKUNG KEPUTUSAN DALAM MENENTUKAN PERUSAHAAN OUTSOURCING PADA SEKRETARIAT SETDA PEMPROV SUMUT DENGAN MENGGUNAKAN METODE PROFILE MATCHING - Sucitra Sidabutar; Bosker Sinaga (Jurnal Media Informatika, 2021)
This research conducted the determination of outsourcing companies at the Secretariat of the Provincial Government of North Sumatra. Outsorcing is an attempt to contract an activity to an outside party to obtain the required job services and outsourcing is an alternative in doing the work itself. To maximize employee performance, discipline and maintain infrastructure facilities to the maximum at the General Bureau of the Provincial Government of North Sumatra need the selection of a good outsourcing company. The method used in analyzing data is the profile matching method. From the results of data analysis, the outsourcing company selected is PT. Arcana with a total value of 4.33. In accordance with the formulation of the problem and the purpose of the study, the researchers drew conclusions, namely in the profile matching method in the decision support system determining the outsourcing company at the Secretariat of the Provincial Government of North Sumatra must follow the steps of the work of profile matching, namely the determination of alternatives, aspects, criteria, profile assessment of each aspect on each alternative, calculation of gap mapping.